2022
DOI: 10.1038/s41564-022-01153-5
|View full text |Cite
|
Sign up to set email alerts
|

The DarTG toxin-antitoxin system provides phage defence by ADP-ribosylating viral DNA

Abstract: Toxin-antitoxin (TA) systems are broadly distributed, yet poorly conserved, genetic elements whose biological functions are unclear and controversial. Some TA systems may provide bacteria with immunity to infection by their ubiquitous viral predators, the bacteriophage. To identify such TA systems, we searched bioinformatically for those frequently encoded near known phage defense genes in bacterial genomes. This search identified homologs of DarTG, a recently discovered family of TA systems whose biological f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
112
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 121 publications
(117 citation statements)
references
References 45 publications
4
112
0
1
Order By: Relevance
“…Such mutations allowed phages to escape the systems Lamassu, Hachiman, ietAS , Retron-Eco8, ShosTA, Borvo, and some AVAST systems (Figure 3, Figure 6). Previous studies on the anti-phage defense systems AbiK (Bouchard and Moineau, 2004; Wang et al, 2011), AbiQ (Samson et al, 2013b), ApbA/B (Yasui et al, 2014), DarTG (LeRoux et al, 2022), Tin (Mosig et al, 1997), and Nhi (Bari et al, 2022) have also reported phage escape via mutation in one of these core replication proteins. Thus, diverse defense systems have evolved to sense or target the core determinants of phage replication.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Such mutations allowed phages to escape the systems Lamassu, Hachiman, ietAS , Retron-Eco8, ShosTA, Borvo, and some AVAST systems (Figure 3, Figure 6). Previous studies on the anti-phage defense systems AbiK (Bouchard and Moineau, 2004; Wang et al, 2011), AbiQ (Samson et al, 2013b), ApbA/B (Yasui et al, 2014), DarTG (LeRoux et al, 2022), Tin (Mosig et al, 1997), and Nhi (Bari et al, 2022) have also reported phage escape via mutation in one of these core replication proteins. Thus, diverse defense systems have evolved to sense or target the core determinants of phage replication.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the phage mutants we isolated may not escape by mutating the component identified by the defense system, but rather evade immunity via other means. It is possible that some mutations could allow the phage to overcome the effect of the system, as proposed, for example, in the case of the DarTG system, which installs ADP-ribose on phage DNA in response to infection (LeRoux et al, 2022). Phages mutated in their DNA polymerase could tolerate the effect of the DarTG system, and it was suggested that these mutations allowed the polymerase to replicate DNA despite the DNA modifications made by the DarTG system (LeRoux et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While most bacteria carry at least one restriction enzyme and about half of them encode CRISPR-Cas as part of their immune arsenal, other defense systems are sparsely distributed in microbial genomes (Payne et al, 2021; Tesson et al, 2022). Over sixty anti-phage defense systems have been discovered in the past few years (Doron et al, 2018; Gao et al, 2020; LeRoux and Laub, 2022; Millman et al, 2022; Rousset et al, 2022) and while the mechanisms of action of a minority of them have been determined (Bernheim et al, 2021; Garb et al, 2021; Johnson et al, 2022; LeRoux et al, 2022; Millman et al, 2020; Tal et al, 2022; Whiteley et al, 2019), the vast majority remain unexplored. It is estimated that an average bacterial genome contains more than five defense systems, with some bacteria encoding as many as 57 such systems (Tesson et al, 2022).…”
Section: Introductionmentioning
confidence: 99%